Discourse Studies, Corpus, and Multimodality in Urban Research - Reza Shirazi (Articulo: Journal of Urban Research)
This paper explores the contribution of Discourse Studies (DS) to urban research from two perspectives: the field of inquiry and the research corpus. It investigates which areas have utilised DS in their research and why, as well as which types of discursive modes have been subjected to analysis. An analysis of 126 publications suggests that DS has been widely utilised to investigate urban questions in urban planning and theory, urban policy, housing research, and environmental policy; this capacity can be expanded to other fields of urban research. The study also finds out that the corpus of analysis has mainly remained monomodal, limited to one item or multiple items of the same type, predominantly text-based materials. To address this problem, the corpus of the analysis should be diversified to recognize the multimodality of discourse. This entails encompassing a variety of non-verbal modes such as images, music, gestures, moving images, soundtracks, and 3D objects. The paper concludes by pinpointing directions towards which future research should progress in order to overcome the challenges of utilising DS in urban research.Discourse Studies, Discourse, Urban Studies, Urban Research, Multimodality